Cortical activation during power grip task with pneumatic pressure gauge: an fMRI study - Mohamad, M.; Mardan, N.H; Ismail, S.S (IOP Publishing Ltd, 2017)
Aging is associated with a decline in cognitive and motor function. But, the relationships with motor performance are less well understood. In this study, functional magnetic resonance imaging (fMRI) was used to assess cortical activation in older adults. This study employed power grip task that utilised block paradigm consisted of alternate 30s rest and active. A visual cue was used to pace the hand grip movement that clenched a cylindrical rubber bulb connected with pressure pneumatic gauge that measure the pressure (Psi). The objective of this study is determined the brain areas activated during motor task and the correlation between percentage signal change of each motor area (BA 4 and 6) and hand grip pressure. Result showed there was a significant difference in mean percentage signal change in BA 4 and BA 6 in both hemispheres and negative correlation obtained in BA 4 and BA 6. These results indicate that a reduced ability in the motor networks contribute to age-related decline in motor performance.